Physiological Organ Profile of Broilers Added Fermented Extract of Bitter Leaves (Vernonia amydalina) in Drinking Water - Nilawati; Nelzi Fati; Eva Yulia; Toni Malvin; Ramaiyulis (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
The use of AGP (Antibiotic Growth Promoter) in several countries has been widely banned in broiler cultivation, thus triggering experts to discover the use of medicinal plants as antibiotics and natural broiler growth promoters. One of the active substances that function as AGP is flavonoids. Bitter leaves are one of the medicinal plants containing saponins, tannins and flavonoids which have functions as antibacterial, antifungal, antidiabetic, antiplasmodial and anticarcinogenic. The aim of the study was to determine the effect of adding fermented Bitter leaf extract (Vernonia amygdalina) to drinking water on the physiological organs of broilers, and to determine the correct dose of adding fermented Bitter leaf extract to drinking water on physiological organs of broilers. The research results obtained were the addition of fermented extract of  Bitter leaves (Vernonia amygdalina) in drinking water had no significant effect (P>0.05) on the percentage of broiler heart, liver and spleen. The addition of fermented  Bitter leaf extract (Vernonia amygdalina) up to 15% in drinking water can be tolerated against the heart, liver and spleen in broiler drinking water. The addition of fermented Bitter leaf extract has a good effect on internal organs, namely the heart, liver and spleen.